Natural Chalcones in Chinese Materia Medica: Licorice - Wang, Danni (Evid Based Complement Alternat Med, 2020)
Licorice is an important Chinese materia medica frequently used in clinical practice, which contains more than 20 triterpenoids and 300 flavonoids. Chalcone, one of the major classes of flavonoid, has a variety of biological activities and is widely distributed in nature. To date, about 42 chalcones have been isolated and identified from licorice. These chalcones play a pivotal role when licorice exerts its pharmacological effects. According to the research reports, these compounds have a wide range of biological activities, containing anticancer, anti-inflammatory, antimicrobial, antioxidative, antiviral, antidiabetic, antidepressive, hepatoprotective activities, and so on. This review aims to summarize structures and biological activities of chalcones from licorice. We hope that this work can provide a theoretical basis for the further studies of chalcones from licorice.